2021
DOI: 10.1089/jop.2020.0096
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Persistence with First-Line Therapy and Compliance with Glaucoma Guidelines Using Japanese Health Care/Pharmacy Claims Database

Abstract: Purpose: This study evaluated Japanese patients' adherence to first-line therapy and physicians' compliance with the guidelines (GLs) for glaucoma in daily practice. Methods: This retrospective, noninterventional cohort study used a Japanese health care/pharmacy claims database from 2011 to 2016. We compared adherence based on the primary outcomes assessed as proportion of days covered (PDC) and persistence between patients who received first-line monotherapy followed by secondline fixed-combination therapy (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Also, and as Wolfram et al [20] found, monotherapies, particularly with prostaglandins, and simplified treatment regimens lead to better adherence and persistence. In spite of fixed-combination eye drops may be a convenient treatment option for glaucoma patients according to the patients' medical needs, especially for those who are already at the severe glaucoma stage at the initial glaucoma consultation and need early IOP lowering treatment, for those who are relatively young and for whom it is important to delay blindness, or for those who need personalized medication due to their lifestyle [21] , the initial medication adherence for this anti-glaucoma drugs was lower than for the monotherapy drugs. Our results also show that younger patients were more likely to early discontinue their treatment, after the first dispensing.…”
Section: Discussionmentioning
confidence: 99%
“…Also, and as Wolfram et al [20] found, monotherapies, particularly with prostaglandins, and simplified treatment regimens lead to better adherence and persistence. In spite of fixed-combination eye drops may be a convenient treatment option for glaucoma patients according to the patients' medical needs, especially for those who are already at the severe glaucoma stage at the initial glaucoma consultation and need early IOP lowering treatment, for those who are relatively young and for whom it is important to delay blindness, or for those who need personalized medication due to their lifestyle [21] , the initial medication adherence for this anti-glaucoma drugs was lower than for the monotherapy drugs. Our results also show that younger patients were more likely to early discontinue their treatment, after the first dispensing.…”
Section: Discussionmentioning
confidence: 99%